2013
DOI: 10.1021/ol402229m
|View full text |Cite
|
Sign up to set email alerts
|

γ-Carbonyl Quinones: Radical Strategy for the Synthesis of Evelynin and Its Analogues by C–H Activation of Quinones Using Cyclopropanols

Abstract: Cyclopropanols, on oxidative ring opening with AgNO3-K2S2O8 in DCM-H2O at room temperature and under open flask conditions, produced β-keto radicals which were successfully added to quinones to furnish γ-carbonyl quinones. This mild method has been applied to the synthesis of cytotoxic natural products, 4,6-dimethoxy-2,5-quinodihydrochalcone and evelynin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…The yields are good to excellent and mild conditions are coupled with short reaction times (127). Two methods of introducing the trifluoromethyl group to 1,4-benzo and 1,4-naphthoquinones offer reasonable to good yields under mild conditions.…”
Section: ð36þmentioning
confidence: 99%
“…The yields are good to excellent and mild conditions are coupled with short reaction times (127). Two methods of introducing the trifluoromethyl group to 1,4-benzo and 1,4-naphthoquinones offer reasonable to good yields under mild conditions.…”
Section: ð36þmentioning
confidence: 99%
“…Another important silver catalyzed direct alkylation of quinones was the γ ‐carbonylation of quinones with cyclopropanols. In 2013, Ilangovan and co‐workers found that β ‐keto radicals 19 , which were generated from the oxidation ring opening of cyclopropanols 18 , could be added to quinones to furnish γ ‐carbonyl quinones (Scheme ) . With the assistance of AgNO 3 /K 2 S 2 O 8 oxidant system, cytotoxic natural products, such as 4,6‐dimethoxy‐2,5‐quinodihydrochalcone, evelynin and a series of other highly substituted γ ‐carbonyl quinones could be prepared in 32–80 % yields.…”
Section: Alkylation Of Quinonesmentioning
confidence: 99%
“…Quinones play an important role in organic chemistry because of their unique structure. In 2013, Malayappasamy and co-workers reported an efficient and convenient method for the synthesis of γ-carbonyl quinones 95 via ring-opening and functionalization of cyclopropanols 91 with quinones 94 (Scheme 21) [99]. In this transformation, both AgNO 3 and FeSO 4 were all efficient catalysts for the ring-opening and functionalization reaction.…”
Section: Reviewmentioning
confidence: 99%